Accessing Legacy Phosphorus in Soils - Doydora, Sarah; Gatiboni, Luciano; Grieger, Khara; Hesterberg, Dean; Jones, Jacob L.; McLamore, Eric S.; Peters, Rachel; Sozzani, Rosangela; Van den Broeck, Lisa; Duckworth, Owen W. (Soil systems, 2020)
Repeated applications of phosphorus (P) fertilizers result in the buildup of P in soil (commonly known as legacy P), a large fraction of which is not immediately available for plant use. Long-term applications and accumulations of soil P is an inefficient use of dwindling P supplies and can result in nutrient runoff, often leading to eutrophication of water bodies. Although soil legacy P is problematic in some regards, it conversely may serve as a source of P for crop use and could potentially decrease dependence on external P fertilizer inputs. This paper reviews the (1) current knowledge on the occurrence and bioaccessibility of different chemical forms of P in soil, (2) legacy P transformations with mineral and organic fertilizer applications in relation to their potential bioaccessibility, and (3) approaches and associated challenges for accessing native soil P that could be used to harness soil legacy P for crop production. We highlight how the occurrence and potential bioaccessibility of different forms of soil inorganic and organic P vary depending on soil properties, such as soil pH and organic matter content. We also found that accumulation of inorganic legacy P forms changes more than organic P species with fertilizer applications and cessations. We also discuss progress and challenges with current approaches for accessing native soil P that could be used for accessing legacy P, including natural and genetically modified plant-based strategies, the use of P-solubilizing microorganisms, and immobilized organic P-hydrolyzing enzymes. It is foreseeable that accessing legacy P will require multidisciplinary approaches to address these limitations.